Mental representation of sharing experiments: Analyzing choice and belief data - Werner Güth; Charlotte Klempt; Kerstin Pull (Institut für Angewandte Wirtschaftsforschung (IAW), 2015)
We confront allocator participants with different sharing games in a within subjects design: the Nash demand game, the ultimatum game, the yes-no-game and the impunity game. We allow participants to opt out rather than play the game under consideration. Beside choice data we also collect belief data to learn more about the mental representations of sharing games.
Keywords: 330